A new 12a-hydroxyelliptone from the stems of derris malaccensis - Nopporn Thasana (2018)
A new rotenoid, 12a-hydroxyelliptone (1) and the known rotenoid 12-deoxo-12α-acetoxyelliptone (2) were isolated from the stems of Derris malaccensis. The structures were established by spectroscopic and chemical methods as well as by comparison with published data.